Intellectual Discourse of Nationbuilding: Nationalism and History Writing in India - Yerekesheva, Laura G. (The New Research of Tuva, 2024)
The article analyzes issues related to the intellectual discourse of nation-building in India, which is discussed in the context of theories of nationalism, the “third space” / hybridity and decoloniality. Using the works of Indian researchers devoted to the study of the ancient and modern history of India as a sample, the article defines and analyzes the main patterns associated with the actualization of these theoretical discourses.It shows that the actualization of issues in the field of production of knowledge, meanings and values ​​in India in relation to its ancient past and present went through certain stages, which reflected a change in paradigms — from orientalism through the “third space” to decoloniality. These stages became a reflection of the heated ideological discussions that took place and are taking place in Indian society. From a theoretical perspective, they are markers of the process of activating tradition in the “third space” and its transformation into decoloniality.The historiographic narration of studying the history of archeology in the mid-20th century (Surindranath Roy) reveals the predominantly orientalist discourse and hybridity. In the late 20th — early 21st century, the research on archaeological issues at the junction with the socio-political analysis undertaken by Dilip Chakrabarty shows the preservation of hybridity and an appeal to decoloniality. At present, in the works of Sai Deepak, one can note the domination of the decoloniality concept over the other two discourses. Decoloniality occurs mainly through an appeal to tradition and religion, which becomes a key mode, both content and form, as well as a kind of engine of this process. In turn, this may indicate the long-term nature of the transformation process, the incompleteness of which could be clearly and particularly manifested precisely in the sphere of production of knowledge, meanings, and symbols.
Keywords: nation-building; nationalism; India; orientalism; hybridity; decoloniality